Mindfulness, Interoception, and the Body: A Contemporary Perspective - Gibson, Jonathan (Frontiers in Psychology, 2019)
Mindfulness is often used as an umbrella term to characterize a large number of practices, processes, and characteristics. Critics argue that this broad definition has led to misinformation, misunderstanding, and a general lack of methodologically rigorous research. Some of the confusion surrounding mindfulness is also believed to stem from an undifferentiated use of the term mindfulness and meditation. Mindfulness and all other forms of meditation have been shown to modulate the insula which is the primary hub for interoception. Some have argued that interoception is foundational to mindfulness and may be the primary mechanism by which one benefits from the practice. However, much like the mindfulness literature, interoception remains broadly defined often without precision and with domain-specific meanings and implications. Research demonstrates that the insula and surrounding neural circuits are believed to be responsible for a number of other functions beyond interoception including attention, awareness, and all subjective experiences, much of which has been linked to the mindfulness literature. It has been assumed that mindfulness produces these neuroplasticity and functional effects. There is evidence that mindfulness and some of its benefits may be better described as increased interoception as a result of the neuroplasticity changes in the insula, and the development of the insula and surrounding neural circuits may cultivate dispositional mindfulness. The purposes of this paper are to (1) highlight that it may be more accurate to link many of the identified benefits in the mindfulness literature to interoception and its neurological correlates, and (2) propose attentional style as a means to clarify some of the confusion surrounding mindfulness, interoception, and meditation. Different meditations and require different attentional styles. Attention can be analogous to a focal point with each focal point providing a unique perspective. Given that all meditative techniques modulate the insula, each meditation can provide a unique perspective from which to investigate complex interoceptive signals that may be unavailable from other meditative traditions. It may prove more useful to anchor scientific findings in the concrete body as a means to investigate those rather than a set of abstract, broadly defined meditative techniques.